Insects and society - Schowalter, Timothy Duane, 1952- (CRC Press, 2019)
"Insects are the most species-rich and important organisms on earth, and that's why there are many university courses dedicated to the topic of Insects and Society. But, surprisingly, this is the first textbook specifically created for those courses. The content in this textbook is not only ideal for introductory courses, but it also is great for K12 instructors, insatiably curious children, and indeed anyone fascinated by insects and their impact on people." - Robert K. D. Peterson, Ph.D., Professor of Entomology, Montana State University and Past President, Entomological Society of America "Society is undervaluing the role of insects as pivotal drivers of ecosystem functioning and services. Addressing this deficit is a major merit of this book." - Teja Tscharntke, Professor and Head of the Agroecology Research Group at the University of Göttingen, Germany Insects are all around us, outweighing humanity by 17 times. Many are nuisances; they compete with us for food and carry some of our most devastating diseases. Many common pests have been transported worldwide by humans. Yet, some recent reports suggest dramatic declines in some important groups, such as pollinators and detritivores. Should we care? Yes, we should. Without insect pollinators we'd lose 35% of our global food production; without detritivores, we would be buried in un-decayed refuse. Insects are also critical sources for nutritional, medical and industrial products. A world without insects would seem a very different and unpleasant place. So why do insects inspire such fear and loathing? This concise, full-color text challenges many entrenched perceptions about insect effects on our lives. Beginning with a summary of insect biology and ecology that affect their interactions with other organisms, it goes on to describe the various positive and negative ways in which insects and humans interact. The final chapters describe factors that affect insect abundance and approaches to managing insects that balance their impacts. The first textbook to cater directly to those studying Insect and Society or Insect Ecology modules, this book will also be fascinating reading for anyone interested in learning how insects affect human affairs and in applying more sustainable approaches to "managing" insects. This includes K-12 teachers, undergraduate students, amateur entomologists, conservation practitioners, environmentalists, as well as natural resource managers, land use planners and environmental policy makers.